The returns to vocational training and academic education: Evidence from Tanzania. - Kahyarara, G; Teal, F (CSAE (University of Oxford), 2008)
In this paper we ask what can account for the continuing strong preference for academic education in Africa where the level of development is so low and there are few wage jobs and which form of educational investment, the academic or vocational, is most profitable. We argue that the answers to these questions are linked through the shape of the earnings function and the importance of firm effects. High levels of academic education have far higher returns than those available either from vocational or lower levels of academic. However at lower levels the vocational return can exceed the academic.